Ultrasound-Promoted Pyruvic Acid Catalyzed Green Synthesis of Biologically Relevant Bis(Indolyl)Methanes Scaffold under Aqueous Condition. (21st October 2022) - Deshmukh, Santosh R.; Nalkar, Archana S.; Thopate, Shankar R.
Abstract: An efficient and green protocol has been introduced for the synthesis of medicinally important bis(indolyl)methane derivatives using pyruvic acid catalyst in the presence of water. Pyruvic acid catalyzes the reaction of aldehyde with indole efficiently and products were obtained in good to excellent yields under sonication (50 °C) or under conventional heating (80 °C). The advantages of this synthetic methodology are use of environmental-friendly, commercially available, biodegradable catalyst, short reaction times, Lewis acid-free and metal-free mild reaction conditions with excellent yields and is compatible with a wide range of electronically diverse substrates. Pyruvic acid in water as a catalyst under ultrasound radiation can be a better alternative to synthesize bis(indolyl)methane derivatives than some of the traditional methods. Graphical Abstract: UF0001